2021
DOI: 10.1111/tmi.13700
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of seafood‐related food poisoning from undetectable Vibrio parahaemolyticus‐like pathogen, Chiang Mai Province, Thailand, December 2020

Abstract: Objective: On 1 December 2020, the Department of Disease Control of Thailand was notified of a cluster of food poisoning cases among participants at a church festival in Mae Ai district, Chiang Mai province. We conducted an outbreak investigation to confirm diagnosis, describe the epidemiological characteristics of the outbreak, identify possible sources of the outbreak and provide appropriate control measures. Methods:We reviewed medical records of the food poisoning cases from the health care centres. Active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Many studies and reports [28][29][30][31][32] have found that intestinal cramping, diarrhea, vomiting, anxiety, chills and breathing difficulties are common signs of foodborne illnesses. These signs are caused either by consumed microorganisms, or toxic infections, such as Clostridium perfringens [33,34], or by microbial toxins produced by the microorganisms [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies and reports [28][29][30][31][32] have found that intestinal cramping, diarrhea, vomiting, anxiety, chills and breathing difficulties are common signs of foodborne illnesses. These signs are caused either by consumed microorganisms, or toxic infections, such as Clostridium perfringens [33,34], or by microbial toxins produced by the microorganisms [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Historically linked to seafood, such as shrimp, oysters, clams, and cockles, V. parahaemolyticus received recognition for its pathogenic potential in humans in 1950 following a major outbreak in Japan in which contaminated sardine with the bacterium led to 20 fatalities and 270 hospitalizations [7]. Subsequently, outbreaks stemming from the consumption of raw or undercooked seafood tainted with V. parahaemolyticus have been documented in various countries, including the USA, Thailand, Vietnam, China, Spain, and Chile [8][9][10][11][12][13]. The disease pathogenesis of V. parahaemolyticus infections is caused by virulence factors such as thermostable direct hemolysin (TDH) or TDH-related hemolysin (TRH), encoded by tdh and trh genes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses commonly reported are Norovirus and Hepatitis A, while examples of parasites involved are Cryptosporidium spp, Giardia lamblia , Trichinella spiralis , Cyclospora spp, Toxoplasma canis, and Entamoeba histolytica ( Stryinski et al, 2020 ; Bozkurt et al, 2021 ; Lee and Yoon, 2021 ; Segeritz et al, 2021 ; Patel et al, 2022 ). Typical symptoms of foodborne illness include abdominal pain, diarrhea, vomiting, nausea, fever, difficulty breathing, and even death in severe cases ( Abebe et al, 2020 ; Aik et al, 2020 ; Myintzaw et al, 2021 ; Sun et al, 2021 ; Janekrongtham et al, 2022 ). These symptoms are caused by ingested pathogens, such as foodborne infections ( Salmonellosis , Listeriosis , etc.)…”
Section: Introductionmentioning
confidence: 99%